A teaching sequence granting space to the students’collaborative creation in the music classroom: some observations - Giglio, Marcelo; Perret-Clermont, Anne-Nelly (My University, 2010)
Classical traditions of research have generally been centered on the individual processes of musical composition. Our aim is to look at collective processes in order to understand how to provide space for creativity in music education in school. Activity theory, socio-cognitive research on learning, new curricula, analyses of student-teacher interaction and recent studies on collaborative creativity inform our research questions about the spare space usually allocated for students' collaborative creation in the music lesson. We proceed by designing teaching sequences that invite pupils aged 11-13 to work together and compose a piece of music. We observe what happens via video and we make a descriptive analysis of the data: how pupils distribute the tasks amongst themselves; how agreements and disagreements arise when children compose together and write it down. Usually conflicts are solved implicitly or explicitly via the chidren's engagement in efforts to manage the composition together. They make comments that are sometimes relevant and sometimes not. This study helps to understand some of the cognitive moves and social interactions that happen in such an activity. It will give us a basis for reconsidering the importance of the teacher's role in creating and supporting this type of creative interaction in the classroom.
, Poster presented at the 29th ISME World Conference, Beijing, China
Keywords: Collaborative activity; creativity; music; social interaction; learning.